Contribuição com a cadeia produtiva da pesca: beneficiamento de massa de macarrão sem glúten à base de Surimi - Garcia Cafiero, Joyce Tarsia (2018)
Brazil needs to take advantage of fishing resources by developing socially innovative products with technical-scientific knowledge, high value-added, low production costs and cultural identity. The challenge of this thesis was to make a gluten-free surimi fresh pasta, similar to macaroni. The surimi is a protein concentrate extracted from fish. Therefore, it was used fish surpluses caught by the fishing communities, or from aquaculture cultivation, or low market value fish. Twenty-four formulations of the surimi mass (proportions ranging from 70 to 90%) were produced on a handmade scale, with different sorts of starches such as maize, rice, potatoes and cassava, (proportions ranging from 5 to 10%) and fresh or powdered egg white, suitable for different conditions of the productive processes (mixture, Grinding, formatting, heat treatment, slicing and packaging). Proximate (ash, proteins and humidity) and sensory (texture and color) analysis, as well as the determination of the nutritional values and cost of the ingredients, were carried out. Interviews with the fishing communities in the municipalities of Mangaratiba, Arraial do Cabo and Cabo Frio were conducted aiming to collect social data in order to plan the workshops, evaluation of sensory acceptance and intention to produce/sell the product. The results showed that different types of starches, and the conditions of the process, interfered with both the texture and the slicing of the Surimi mass. The percentage of ash, protein and humidity, ranged from 2 to 3%, 16 to 25% and 71 to 78%, respectively. It was noticed that fish is not the most consumed protein source as the co-products of fish such as kibbe, fishballs, nuggets and fish burgers were tasted at the workshops. However, the interest to develop new products and make full use of the fish was shown afterwards. On a scale of 0 to 5 the intention of producing/selling surimi noodles was averaging 4.7 and the overall aspect reached 4.3. The process of surimi mass production was carried out in the public food systems (schools and community production) with easy-to-purchase equipment. However, it was reported that the preparation of the surimi is a bit laborious and time-consuming. Nevertheless, the result was satisfactory and positively impactful. This research allowed the actors involved to know new technologies, giving them the hope of managing new ventures and creating new products.